Cellular and humoral influenza-specific immune response upon vaccination in patients with common variable immunodeficiency and unclassified antibody deficiency. Issue 21 (5th May 2016) - Hanitsch, Leif G.; Löbel, Madlen; Mieves, Jan Florian; Bauer, Sandra; Babel, Nina; Schweiger, Brunhilde; Wittke, Kirsten; Grabowski, Patricia; Volk, Hans-Dieter; Scheibenbogen, Carmen
Highlights: Most patients with antibody deficiency mount no antibody response to influenza vaccination. T cell response against influenza in patients with CVID and unclassified antibody deficiency is comparable to healthy controls. Annual vaccination against influenza is recommend in CVID and unclassified antibody deficiency. Abstract: Background: Immunization against seasonal influenza with inactivated vaccine is recommended for patients with common variable immunodeficiency (CVID). However, humoral vaccine response in CVID patients is frequently impaired and current knowledge on T cell vaccine response in CVID and other patients with antibody deficiency is poor. Objective: In the present study, we comparatively analyzed the antibody and T cellular immune response of patients with CVID and unclassified antibody deficiency to influenza vaccination in the season 2013–2014. Methods: Eight patients with CVID, 8 patients with unclassified antibody deficiency and 9 healthy controls were vaccinated with a single dose of non-adjuvanted seasonal influenza vaccine. Before and 3 weeks after the vaccination antibody titers against the strains A/California/7/2009, A/Texas/50/2012, and B/Massachusetts/02/2012 included in the vaccine were measured by hemagglutination inhibition testing. Additionally, vaccine-specific T cell cytokine response was determined by stimulation with the complete vaccine in vitro . Results: Whereas all healthy controls responded to vaccination with serum antibody titers, only 1/8 CVID patients and 4/8 patients with unclassified antibody deficiency showed a response against at least 1 of the 3 vaccine strains. However, 7/8 of the CVID and 6/8 of the patients with unclassified antibody deficiency had similar frequencies of vaccine-induced IFN-γ, TNF-α and IL-2 producing CD40L + T cells as the control group. Conclusion: Our data suggest that most CVID and unclassified antibody deficiency patients benefit from seasonal influenza vaccination by mounting a cellular response.